2020
DOI: 10.3389/fonc.2020.01648
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Chloride Intracellular Channel 4 Expression Is Associated With Adverse Outcome in Cytogenetically Normal Acute Myeloid Leukemia

Abstract: Background and Methods: Acute myeloid leukemia (AML), which starts in the bone marrow, is a group of hematopoietic stem cell disorders. Chloride intracellular channel 4 (CLIC4) is regulated by p53, c-Myc, and TGF-β. It induces the NF-κB-dependent activation of HIF (hypoxia-inducible factor) and participates in tumor growth through its microenvironmental function. However, its prognostic value in AML remains unclear, as well as its co-expression biomarkers. In this study, we evaluated the prognostic significanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Some of the cells became epithelial at the bottom of the graph, defined by transcripts associated with epithelial-to-mesenchymal transition such as S100A4 . Other cells progressed toward early hematopoietic cells, propelled by key bone marrow niche–associated transcripts such as RNPEP ( 31 ) and cytokinesis factors such as CLIC4 ( 32 ). Cells directly after this decision point (clusters 4, 20, and 21) were characterized by the expression of ribosomal transcripts, which also characterized the end of the trajectory toward mature MKs, indicating increased protein synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the cells became epithelial at the bottom of the graph, defined by transcripts associated with epithelial-to-mesenchymal transition such as S100A4 . Other cells progressed toward early hematopoietic cells, propelled by key bone marrow niche–associated transcripts such as RNPEP ( 31 ) and cytokinesis factors such as CLIC4 ( 32 ). Cells directly after this decision point (clusters 4, 20, and 21) were characterized by the expression of ribosomal transcripts, which also characterized the end of the trajectory toward mature MKs, indicating increased protein synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Carofino et al demonstrated that CLIC4 expression in tumor tissue was attenuated due to the production of microRNA-142-3p from infiltrating immune cells in a squamous cell carcinoma xenograft model mouse (37). Moreover, Huang et al suggested that CLIC4 is regulated by microRNAs, transcriptomes, and signal pathways in human acute myeloid leukemia (17). Both malignant epithelial and stromal tissues may be consecutively exposed to CLIC4-targeting microRNAs during the progression of colorectal lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, several studies had demonstrated that CLIC4 expression is regulated by factors such as tumor suppressor p53, c-MYC, tumor necrosis factor (TNF)-α, and transforming growth factor (TGF)-β, and is expressed during cell differentiation and DNA damage (4, 8-10). CLIC4 positively or negatively affects the signals of Kirsten-ras (KRAS) and p38 mitogen-activated protein kinase (MAPK), induction of inducible nitric oxide synthase, apoptosis, cell growth, cell migration, invasion, epithelial mesenchymal transition (EMT), immune function, loss of mitochondrial membrane potential, endoplasmic reticulum stress, microRNAs, hypermethylation and tumorigenesis, as well as through differentiation of myofibroblasts and formation of the tumor microenvironment (TME) (7,(11)(12)(13)(14)(15)(16)(17)(18). However, the function of CLIC4 depends on the type of cancer, and its variation in each cell remains elusive.Worldwide, colorectal cancer (CRC) is a disease that exhibits a high incidence as well as mortality rate (19).…”
mentioning
confidence: 99%
“…The expression levels of CLIC4 and GAS2L1 were found to be higher in circulating tumor cells (CTCs) from pancreatic cancer patients compared to peripheral blood mononuclear cells [93]. Besides, the overexpression of CLIC4 was associated with unfavorable outcomes in multiple cohorts of CN-AML patients [33].…”
Section: Pathway 3: Ctla4-cd2mentioning
confidence: 99%